The Role of Indonesian Credit Cooperatives Towards Strengthening Financial Literacy and Improving Financial Behavior - Daniel Adi Setya Rahardjo; Suwardi Suwardi (AKUNTANSI 45, 2022)
This study examines the effect of financial literacy on the financial behavior of Credit Union (CU) members in Indonesia in realizing the 2021-2025 SNLKI strategic direction. This exploratory study uses convenience sampling taken from the members of CU in Indonesia. The reason for selecting respondents is the availability of very abundant data. The process of collecting data was by distributing questionnaires via email to members of credit unions in Kalimantan and Java. Questionnaires were randomly sent to Credit Union members over the age of 18. Data analysis used SurveyMonkey and data processing used the Microsoft Excel program which was sent to researchers. The results of the study found a positive relationship between financial literacy and financial behavior.